G488(P) Absence of dna polymerase chain reaction in neonatal blood cultures could lead to earlier discharge, better antibiotic stewardship and significant financial savings. (24th May 2017) - Shaw, E; Bullivant, J; Ridgeway, E; Clark, S; Pilling, E
Abstract : Background: Newborns with risk factors for early onset sepsis are treated with intravenous antibiotics until a negative blood culture result. The absence of fungal and bacterial deoxyribonucleic acid polymerase activity could indicate a negative result during blood culture incubation. Cognitor Minus looks for DNA polymerase activity and is designed to report negative samples after 12 hours of incubation. A non-negative result is reported as 'not determined'. Aims: We piloted if Cognitor Minus could lead to earlier detection of negative results in well newborns on the postnatal wards. Methods: Our laboratory ran parallel validation analysis on neonates with sepsis risk factors. All infants were clinically managed using the 36 hours blood culture result to determine negativity. The results from Cognitor Minus and time difference of reporting were compared with our current system. Results: 116 samples had parallel analysis. 90 were in well postnatal babies, who had a blood culture result. Cognitor Minus gave no false negatives. There were 82 negative results with 8 not determined, giving a 100% specificity for negative blood culture result, with a 91.1% negative predictive value. 12 infants were treated for 5 days despite a negative blood culture result due to an elevated CRP, this did not correlate with the 'not determined' results. Cognitor Minus came to a negative result on average 10 hours 8 min earlier (95% confidence intervals 8:55–11:21 hours). Discussion: Clinical implementation of this system could reduce antibiotic exposure and length of stay. This would have potential savings for healthcare providers. Our study estimated a saving of £47 000 PA for the NHS trust. A further study is needed to investigate the safety of DNA microbial polymerase detection for clinical use as our population had no positive blood culture samples. Our current work is using samples from babies admitted to neonatal intensive care with a higher expected proportion of positive blood culture samples to ensure the tests ability to detect a positive sample.